2011
DOI: 10.1111/j.1460-9592.2011.03579.x
|View full text |Cite
|
Sign up to set email alerts
|

Increases in heart rate and systolic blood pressure in anesthetized dogs affected with X‐linked muscular dystrophy after cisatracurium administration: a retrospective study

Abstract: In this report, increases in HR and SAP could be associated with the administration of cisatracurium in individuals affected with X-linked muscular dystrophy. These cardiovascular changes deserve further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Jurado, Mosing, Kutter, Boretti, and Bettschart‐Wolfensberger () observed increases in heart rate and mean arterial blood pressure in a dog after a cis‐atracurium overdose. Staffieri, Sleeper, and Larenza () also observed increases in arterial blood pressure and heart rate in dogs affected by X‐link muscular dystrophy. In the present study, increases in HR and arterial blood pressure were seen 5 min after cis‐atracurium administration in the pig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Jurado, Mosing, Kutter, Boretti, and Bettschart‐Wolfensberger () observed increases in heart rate and mean arterial blood pressure in a dog after a cis‐atracurium overdose. Staffieri, Sleeper, and Larenza () also observed increases in arterial blood pressure and heart rate in dogs affected by X‐link muscular dystrophy. In the present study, increases in HR and arterial blood pressure were seen 5 min after cis‐atracurium administration in the pig.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, increases in HR and arterial blood pressure were seen 5 min after cis‐atracurium administration in the pig. Cis‐atracurium is now known to have antagonistic effects on M2 muscarinic receptors (Sanches Bornia, Bando, Machinski, Pereira, & Alves‐Do‐Prado, ; Staffieri et al., ). These effects on M2 receptors could result in increases in heart rate and arterial blood pressure if high doses of cis‐atracurium are administered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have revealed that DMD patients often show low systolic blood pressure [ 16 , 17 ], and DMD patients with heart failure are also more susceptible to angiotensin receptor/neprilysin inhibitor with recurrent hypotension until discontinuation of this medication [ 6 ], suggesting that DMD might play a critical role in regulating blood pressure. However, a previous dog study [ 18 ], which generated some controversy, reported significantly increased systolic blood pressure in anesthetized dogs affected with X-linked muscular dystrophy (GRDM) after the administration of cisatracurium, a non-depolarizing neuromuscular blocking drug [ 18 ]. In this study, we compared blood pressure between DMD mut and control mice, and found that DMD mut mice exhibited lower blood pressure compared to their wide-type controls ( Figure 2 ), which addressed the role of DMD in the regulation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Cis‐atracurium has been shown to behave in vitro as a type 2 atrial muscarinic receptor (M2) antagonist (Staffieri et al. 2011).…”
mentioning
confidence: 99%
“…2011). The effects of M2 antagonism results in increased HR and APs in anaesthetized dogs affected by X‐linked muscular dystrophy (Staffieri et al. 2011).…”
mentioning
confidence: 99%